Prinsip Legalitas, Necessitas, dan Proporsionalitas dalam Penggunaan Kekuatan oleh Kepolisian: Studi terhadap Implementasi Perkap No.1 Tahun 2009 - I Putu Yogi Revaldi; Yasarman Yasarman (LPPM Iblam School of Law, 2025)
The principle of legality, necessity, and proportionality serves as the foundation for the use of force by law enforcement, ensuring that actions taken remain within the boundaries of justice and human rights. The implementation of these principles is regulated under Chief of Police Regulation No. 1 of 2009, yet its application in practice often encounters challenges. Issues such as discrepancies between regulations and field practices, lack of legal comprehension among officers, and weak accountability mechanisms contribute to the ineffectiveness of the regulation. This study examines how these principles are applied in police operations and evaluates the extent to which the existing legal framework ensures proportional and responsible use of force. This research employs a qualitative method with a normative juridical approach, focusing on regulatory analysis and the interpretation of legal norms in practice. Data collection is conducted through an extensive literature review, analyzing primary legal sources, academic journals, and relevant legal literature. Findings reveal that while regulations are comprehensive, gaps in enforcement persist due to insufficient training, limited evaluation mechanisms, and a lack of independent oversight. These challenges create inconsistencies in the application of the principles, occasionally leading to excessive use of force. Strengthening police training programs and legal education is crucial to ensure a proper understanding and application of these legal norms. Additionally, an independent supervisory body is recommended to improve accountability and ensure that law enforcement actions align with legal and human rights principles.